Frequency of pyometra in bitches patients of the Small Animals Clinic of the Faculty of Veterinary Medicine of Universidad Nacional Mayor de San Marcos during the period 2009-2013 - Solano C., Norelli (2019)
Clinical records of bitches older than six months that were treated at the Small Animals Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos during the period 2009-2013 were revised to obtain statistical information about the frequency of pyometra and its relationship with age, breed, size and season of the year. Out of 4715 records of bitches, 207 were diagnosed with pyometra, representing an incidence of 4.4 ± 0.6%. A statistical association was found between pyometra and breed, but not with the size of the animal or the season of the year.